Total energy consumption analysis in wireless Mobile ad hoc network with varying mobile nodes - Mohammed Ayad Saad; Sameer A. S. Lafta; Raed Khalid Al-Azzawi; Adnan Hussein Ali; Sameer Alani; M. M. Hashim; Bassam Hasan (Institute of Advanced Engineering and Science, 2020)
The energy protocols that have a mechanisms of shortest path routing considered predominant in the networking scenarios. The interesting matter in the routing protocols designing deal with mobile ad hoc network (MANET) must have an energy efficient network for better network performances. The Performances of such routing protocols that can be assessed will be focused on many metrics like delay, throughput, and packet delivery. MANET is a distribution network, having no infrastructure and network decentralization. There routing protocols are utilized for detecting paths among mobile nodes to simplify network communication. The performance comparison of three protocols are Optimized Link State Routing (OLSR), the second is Ad hoc On-Demand Distance Vector (AODV), while the third is Dynamic Source Routing (DSR) routing protocols concerning to average energy consumption and mobile node numbers are described thoroughly by NS-3 simulator. The nodes number is changing between 10 and 25 nodes, with various mobility models. The performance analysis shows that the suggested protocols are superior in relations to the energy consumption for networking data transmission and the performance of the wireless network can be improved greatly.